Role of educational level in the relationship between Body Mass Index (BMI) and health-related quality of life (HRQL) among rural Spanish women - Guallar-Castillón Pilar; Aragonés Nuria; Pérez-Gómez Beatriz; Carrasco José; García-Mendizábal María; Rodríguez-Artalejo Fernando; López-Abente Gonzalo; Pollán Marina (BMC, 2009)
Abstract Background The impact of obesity on health-related quality of life (HRQL) has been little explored in rural areas. The goal of this study is to ascertain the association between obesity and HRQL among Spanish women living in a rural area, and the influence of their educational level. Methods Cross-sectional study with personal interview of 1298 women (aged 18 to 60) randomly selected from the electoral rolls of 14 towns in Galicia, a region in the north-west of Spain. HRQL was assessed using the SF-36 questionnaire. The association between body mass index (BMI) and suboptimal scores in the different HRQL dimensions was summarised using odds ratios (ORs), obtained from multivariate logistic regression models. Separate analyses were conducted for women who had finished their education younger than 16 years old and women with secondary education to assess differences in the relationship between BMI and HRQL according to educational level. Results Among women with primary or lower education, obesity was associated with a higher prevalence of suboptimal values in the following dimensions: Physical functioning (OR: 1.97; 95%CI: 1.22-3.18); Role-physical (OR: 1.81; 95%CI: 1.04-3.14); General health (OR: 1.76; 95%CI: 1.10-2.81); and Role-emotional (OR: 2.52; 95%CI: 1.27-5.03). In women with higher education, physical functioning was the only dimension associated with obesity (OR: 2.02: 95%CI 0.83-4.97). Conclusion The impact of obesity on women's HRQL is greater among those with a lower educational level. This group registered higher prevalence of obesity and poorer self-perceived health.